The relationship between employee motivation, working environment and training with employee performance - Azliana Rashidah, Abd Rahaman (2018)
This study aimed to examine employees' perceptions on factors relating to employee performance. Three independent variables were involved in this study namely, employee motivation, work environment, and training, whilst the dependent variable was employee performance. This was a quantitative study using questionnaires which were distributed to 459 respondents working at the headquarters of Bank XYZ located in Kuala Lumpur. 308 questionnaires were returned for data analysis using descriptive analysis and correlation. The findings reported that there were significant and strong relationships between working environment and employee performance (r=0.630, p<0.01) and between training and employee performance (r=0.540, p<0.01). The result showed that there was a significant and moderate relationship between employee motivation and employee performance (r=0.423, p<0.01). Implications of the findings and future research were also discussed.